MXene incorporated polymeric hybrids for stiffness modulation in printed adaptive surfaces. (December 2021) - Ankit,; Krisnadi, Febby; Pethe, Shreyas; Lim, Kwang Jen Ryan; Kulkarni, Mohit Rameshchandra; Accoto, Dino; Mathews, Nripan
Abstract: Polymeric materials systems developed for actuators and human-machine interfaces suffer from limitations associated with effective force output due to their low mechanical modulus. New material solutions which can provide intrinsic multi-modal responses are needed to reversibly modulate rigidity; to be flexible, stretchable and bendable one moment, and to be rigid, able to bear load and resist deformation at another moment. Thermally modulated phase transition materials are promising for modulation of mechanical properties; however, they have not been explored for electrically driven shape morphing and responsive surfaces which require favourable electrical properties too. Polymers like polyethylene glycol (PEG) allow for low melting point (56 ℃) and high dielectric constant (10), however they are limited by slow crystallization kinetics and large temperature window. We architect an MXene incorporated PEG-water hybrid which allows for both reduction in melting point and rapid heterogeneous nucleation, which in turn increases the crystallization point. Multimodal response is demonstrated via thermal and electrical input, resulting in modulation of 700 times in Young's modulus, 100 times in flexural modulus and 10 times in hardness as well as large actuation strains ( 28%) at low electric fields ( 0.7 V/µm). They can be printed to create hardness domains, allowing for local and programmable modulation. An all-printed haptic device with an array of 3 × 3 pixels has been demonstrated, capable of independently varying the hardness values for each pixel. Graphical Abstract: MXene incorporated PEG-water hybrids were architected for rigidity modulation. Thermally modulated transitions in mechanical properties – 700 times in Young's modulus, 100 times in flexural modulus and 10 times in hardness – along with electrically modulated shape morphing were demonstrated. Printing of hardness domains for localized programmable modulation has been done. ga1 Highlights: MXene incorporated PEG-water hybrids were architected for multimodal response. Thermally modulated reversible changes in mechanical properties has been demonstrated. Electrically modulated shape morphing with large actuation strain ( 28%) can be achieved. Printing of hardness domains for localized programmable modulation.